COMPARATIVE ANALYSIS OF A PASSIVE SYSTEM WITH AN ACTIVE WATER HEATING SYSTEM BY MEANS OF VACUUM SOLAR COLLECTOR GLASS TUBES - Naranjo, J. D.; Ancines, C. A.; dos Santos, C. F.; Krenzinger, A. (Revista de Engenharia Térmica, 2016)
The importance of renewable energy conversion in heat generation systems is increasing. Being a form of clean energy production, solar water heating systems can substitute part of the electricity consumption in Brazilian energy matrix. Beyond the environmental benefits, the use of such systems brings economic benefits to the country and especially those who use them, saving the use of other energy sources for water heating. In Brazil, the solar water heating is carried out mainly by flat solar collectors, a widely known technology produced in the country at low prices. Nowadays another technology is being used: the evacuated solar collectors. These collectors are being worldwide produced on a large scale and they are imported and inserted at competitive prices in the domestic market. Therefore, it is necessary to understand these systems and their operation to avoid errors in their installation and optimize their use. This work accomplishes a comparative analysis of a solar water heating system composed by a water- in-glass evacuated tube solar collector working in forced circulation, varying the flow, with the same system working in thermosyphon circulation. This comparison was performed by determining the annual energy the system can produce for each type of circulation, which was calculated based on the ISO 9459-2 standard and the climatic data of Porto Alegre city, Rio Grande Do Sul State. To perform these measures, a testing bench was mounted with sensors and measuring instruments which were calibrated before use. The results show that the system with thermosyphon circulation produces more annual energy than the forced circulation system where the water temperature stratification in the thermal reservoir was lower.